Ensuring Consistent Application of SOP for E-KTP Population Administration Services in Sidoarjo Regency: Konsistensi Penerapan Prosedur Operasional Standar (SOP) dalam Layanan Administrasi Penduduk untuk Pembuatan E-KTP di Kabupaten Sidoarjo - Ayu Purbasari; Lailul Mursyidah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to identify and analyze the application of population administration service SOPs for making E-KTP in Candi District. This research is a qualitative descriptive study using purposive sampling technique. In this study, the informant was the head of the public service section as key informants, sub-district staff and the community as informants. Data collection techniques by observation, interviews and documentation. Analyzing techniques of data collection, data reduction, data presentation, drawing conclusions. The results of research in the field of implementing SOPs for population administration services for making E-KTP in Candi District are consistently carried out by service officers to the community as service recipients that carry out the appropriate SOP. Commitment that the awareness of service personnel is running, continuous improvement of SOPs every year. The application of SOPs is not binding, but is carried out properly and is flexible. All important elements in the implementation of SOPs that are carried out All officers who run SOPs are in accordance with and never violate the SOPs that are made and mutually agreed upon, Good documentation. The existence of supporting and inhibiting factors in the implementation of SOPs. Highlights: Consistent application of SOPs: The research findings indicate that the implementation of SOPs for population administration services in Candi District is consistently carried out by service officers, ensuring the appropriate procedures are followed. Commitment to continuous improvement: The study highlights the commitment of service personnel in continuously improving SOPs for population administration services, reflecting their awareness and dedication to providing quality service. Supporting and inhibiting factors: The research identifies the presence of both supporting and inhibiting factors in the implementation of SOPs, emphasizing the importance of understanding and addressing these factors to ensure effective service delivery. Keywords: population administration, E-KTP, SOPs, Candi District, qualitative descriptive study